THE EFFECTIVENESS OF ALBUMIN FROM DIFFERENT EGG POULTRY TO ANTIBACTERIAL ACTIVITY OF ON STAPHYLOCCUS Sp. - Fransiskus Baylon Oles, Permata Ika Hidayati, Dyah Lestari Yulianti (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2016)
ABSTRACT This study was held in 20th October untill 20th December 2016 at Laboratory of Kanjuruhan University. The aim of this study was to evaluate antimicrobial activity of albumin from any various of poultry on Staphylococcus sp. The result of this study expected can be helpful in the field of science, can add insight and knowledge in the field of microbiology, especially on the antibacterial activity of avian egg albumin. The material used in this study were albumin from eggs of several species of poultry and Staphylococcus sp. The eggs used were magelang’s duck eggs, mojosari’s duck eggs, chicken eggs and quail eggs. The determination of antibacterial activity of albumen was conducted by diffusion method. The testing of antibacterial activity from albumin antibacterial of various types of poultry were measured the diameter of zone of inhibition (ZI) of each species of Staphylococcus sp on Nutrient Agar. The sample of this study were all the albumin poultry which contained in the eggs which wsas taken from Dau. The selected eggs must be one day old since the parent spawn. The eggs taken directly from the eggs market and breeders. This study used eight pure eggs which the albumin would be taken. The bacterial which was tested in this study were Staphyloccus epidermis and Staphylococcus aureus. The result showed that the antibacterial activity of albumin mojosari’s duck eggs on Staphylococcus aureus with average 13.58 which showed sign d, antibacterial activity of albumin mojosari’s duck eggs and chicken eggs on Staphylococcus epidermis with averages 13.46 and 13.36 which showed sign c, antibacterial activity of albumin magelang’s duck eggs and quail eggs on Staphylococcus aureus with averages 12.38 and 12.33 which showed sign b and antibacterial activity of chicken eggs and quail eggs on Staphylococcus epidermis with averages 12.20 and 10.73 which showed sign a. The best zone of inhibition (ZI) taken from albumin magelang’s duck eggs with value average 18,06 which showed sign e. The conclusion of the study result showed that there are significant differences with different level percentage about 5%, showed that albumin magelang’s duck eggs has the strongest antibacterial activity. Keywords : albumin, antibacterial activity, Staphylococcus sp